Organizational sustainability and risk management : a practical step-by-step guide - Staaf, Denice Viktoria; Pojasek, Robert B. (Boca Raton : CRC Press, 2024)
'Organizational Sustainability and Risk Management: A Practical Step-by-Step Guide, Second Edition will continue to remind all stakeholders how organizations work through a measurement transformation that affects everything they do including following the International Organization for Standardization's (ISO) Guide for Sustainability and climate change. The book is enriched with a discussion on life cycle thinking that has been introduced in the ISO high-level structure. Discussions on a fundamental change in how organizations approach sustainability and how we view organizational sustainability is covered. This book offers a platform for managing all activities, products, and services tailored to the needs of the organization and presents how important Environmental, Social, and Governance (ESG) is to determine the potential for increased financial growth of organizations that have implemented organizational sustainability'--
Revised edition of Organizational risk management and sustainability, [2017].
First edition was authored by Robert B. Pojasek.
OCLC-licensed vendor bibliographic record.
Keywords: Risk management; Management; Sustainability; TECHNOLOGY / Quality Control; TECHNOLOGY / Manufacturing